The Effectiveness of Islamic Religious Education (PAI) in Developing Environmental Awareness among Junior High School Students in Urban and Rural Areas - Hamidah; Syaiful Anwar; Ali Murtadho (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students’ character, morality, and social awareness. PAI learning is not only oriented toward strengthening spiritual aspects and religious ethics but also encompasses broader dimensions of human life, including awareness of environmental sustainability. The integration of ecological values into PAI learning within the school environment is expected to foster students’ environmental awareness and encourage behavioral changes in preserving and protecting nature. This study aims to analyze the effectiveness of PAI learning in developing students’ environmental awareness. The research employs a qualitative approach with a descriptive comparative design. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that PAI learning is effective in fostering students’ environmental awareness. The implementation of PAI learning in developing environmental awareness is carried out through the stages of planning, implementation, and evaluation, which are systematically designed and integrate religious values related to human responsibility in preserving the natural environment. Therefore, PAI learning contributes not only to strengthening students’ theological awareness but also to developing ecological attitudes in their daily lives. This study recommends that future research examine the integration of environmental values in PAI learning using quantitative or mixed-method approaches and expand the research context across various educational levels and school environments to obtain a more comprehensive understanding of its influence on students’ pro-environmental behavior.